2013
DOI: 10.1111/jsm.12286
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Surgery for Female Genital Mutilation Starts Sexual Functioning in Sudanese Woman: A Case Report

Abstract: Introduction Female genital mutilation (FGM) involves the partial or complete removal of the external female genitalia and/or other injury to the female genital organs whether for cultural or other nontherapeutic reasons. Aims The study aims to describe the method of and findings from reconstructive surgery for FGM victims. Methods We present a case of a 24-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Reconstructive surgery was done for a woman aged 24 years old suffered from the large vulval mass for the last 6 years due to female genital mutilation. Also, a girl age 7 years old presented with necrotising fasciitis case as a result of female genital mutilation was reported from Kassala New Hospital in eastern Sudan [ 27 ][ 28 ]. In different study assessed the knowledge and the risk factors associated with HIV among the participants attending the counselling and testing centre in Sudan, they reported that female circumcision is one of the risk factors associated with HIV [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive surgery was done for a woman aged 24 years old suffered from the large vulval mass for the last 6 years due to female genital mutilation. Also, a girl age 7 years old presented with necrotising fasciitis case as a result of female genital mutilation was reported from Kassala New Hospital in eastern Sudan [ 27 ][ 28 ]. In different study assessed the knowledge and the risk factors associated with HIV among the participants attending the counselling and testing centre in Sudan, they reported that female circumcision is one of the risk factors associated with HIV [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…transgender individuals), cosmetic, burn, and even hand surgery populations [1117]. Restoring an impaired (genital) body image can be a primary motivation for patients to opt for plastic reconstructive surgery [1820]. In contrast to what patients may experience, many surgeons (possibly including many non-responders of this study) assume that sexuality is not an issue within their patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive surgery for women who suffer sexual consequences from FGM resulted feasible, with a high degree of acceptance and satisfaction. It restores some of women's natural genital anatomy and offers the potential for improved female sexuality (36).…”
Section: Discussionmentioning
confidence: 99%